Blind maskine og gakket klovn: Komiske fremstillinger af arbejderen fra taylorismen til i dag - Schmidt, Johanne Gormsen (Passage - Tidsskrift for litteratur og kritik, 2018)
Blind Machine and Zany Clown – Comical Representations of the Worker in the Age of Taylorism and Today This article aims at historicizing the conception of the comical, arguing that theories and cultural representations of the comical character from different time periods offer valuable insight into the experience of work at given historical moments. The status of personality in the comical character turns out to be highly pertinent to the understanding of work in the transition to late modernity.